EARTHEN ARCHITECTURE IN PUNA DE ATACAMA, ARGENTINA: LOCAL KNOWLEDGE AND PRACTICES - Tomasi, Jorge (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Earthen building techniques form a corpus of relevant technical and social knowledge that has not always been nor is duly recognized. A signiicant issue about these techniques is that they assume, in Latin America, a remarkable diversity in both names and speciic procedures. This great variability, which often acts as an identifying brand differentiating between different societies, arises from the recognition of needs and possibilities, as well as the particular historical trajectories of these societies. Diversity of local knowledge is then established as a value of earthen building, which must be recognized and sustained. In this paper, the characteristics of earthen building techniques used in the area of Susques, in Puna de Atacama, province of Jujuy (Argentina) will be analyzed. These techniques will be understood and described within an integrated construction system that ranges from stone and earthen foundation, the use of adobe, and even rooing, made of earth and guaya (straw). The particularities of each of these techniques, as well as their interrelation, will be discussed. The transformations that have occurred to procedures and materials in recent years will be considered as well. The starting point will be the understanding of the act of building, which is not only embedded for technical reasons, but fundamentally is a social fact that interlocks with other dimensions of people’s life within a society. Also in this regard, the sociability that comes into play in the construction practice of Susques is considered. The material presented in the text comes from continuous ethnographic ieldwork in Susques since 2003.